The Rise and Resilience of Telegram: An Examination of its Origins, Current Positioning, and Future Prospects in the Context of Russian Realities - Avetisyan, Mane (Advances in Social Sciences Research Journal, 2024)
In recent years, Telegram has emerged as a significant global phenomenon, driven by its innovative approach and commitment to freedom of speech. Founded by Pavel Durov following his contentious departure as CEO of VKontakte, Telegram represents a paradigm shift in messaging platforms, characterized by its predominantly open-source nature, global distribution, and reliance on cloud-based infrastructure. This architectural choice has endowed Telegram with remarkable resilience against censorship attempts, particularly those instigated by the Russian government. This paper delves into the circumstances precipitating Telegram’s inception, analyzing the strategic decisions and underlying motivations that shaped its development. Furthermore, it evaluates Telegram’s current status within the Russian digital landscape, exploring its role as a bastion of free expression amidst increasing governmental scrutiny and control. Additionally, the paper examines the reactive measures employed by Russian authorities to regulate the internet, juxtaposing these efforts with Telegram’s steadfast commitment to providing unfettered communication channels.